Lin28 reprograms inner ear glia to a neuronal fate - Kempfle, Judith S.; Luu, Ngoc‐Nhi C.; Petrillo, Marco; Al‐Asad, Reef; Zhang, Andrea; Edge, Albert S. B. (Stem cells (Dayton, Ohio), 2020)
Sensorineural hearing loss is irreversible and can be caused by loss of auditory neurons. Regeneration of neural cells from endogenous cells may offer a future tool to restore the auditory circuit and to enhance the performance of implantable hearing devices. Neurons and glial cells in the peripheral nervous system are closely related and originate from a common progenitor. Prior work in our lab indicated that in the early postnatal mouse inner ear, proteolipid protein 1 (Plp1) expressing glial cells could act as progenitor cells for neurons in vitro. Here, we used a transgenic mouse model to transiently overexpress Lin28, a neural stem cell regulator, in Plp1‐positive glial cells. Lin28 promoted proliferation and conversion of auditory glial cells into neurons in vitro. To study the effects of Lin28 on endogenous glial cells after loss of auditory neurons in vivo, we produced a model of auditory neuropathy by selectively damaging auditory neurons with ouabain. After neural damage was confirmed by the auditory brainstem response, we briefly upregulated the Lin28 in Plp1‐expressing inner ear glial cells. One month later, we analyzed the cochlea for neural marker expression by quantitative RT‐PCR and immunohistochemistry. We found that transient Lin28 overexpression in Plp1‐expressing glial cells induced expression of neural stem cell markers and subsequent conversion into neurons. This suggests the potential for inner ear glia to be converted into neurons as a regeneration therapy for neural replacement in auditory neuropathy. We have shown here for the first time that transient upregulation of Lin28 can reprogram Plp1 positive inner ear glial cells into neurons in vitro and in vivo in a mouse model of auditory neuropathy.